Authorities and Society vs. Financial Crime in the Gomułka Period in Poland - Jarosz, Dariusz (Studia Historiae Oeconomicae, 2016)
The pivotal motive behind financial crime in the real socialist states was the chronic shortage of goods and services. In the case of Poland under the Gomułka administration (1956-1970), a factor which contributed to the prevalence of practices considered economically criminal was, ironically, the liberalization of the government in the period following Władysław Gomułka’s rise to power. The procedure of issuing new licenses to private and co-operative manufacturing businesses fostered illegal practices, because the new businesses needed supplies of deficit resources. Private trade businesses struggled with similar problems. The authorities tried to prevent financial crime by concentrating on publishing new laws which allowed heavy punishment for those behind the biggest economic scandals. In this field, the penal policy was shaped by the top authorities of the communist party, and their decisions were binding for the institutions of the justice system. Such decisions of the top authorities of the Polish United Workers’ Party (PUWP) were behind the death sentence for Stanisław Wawrzecki, who was charged with fraudulence in meat trade in Warsaw. Poles’ attitude towards financial crime was not clear-cut. One the one hand, in their letters to authorities, many Poles expressed their support for severe punishment for those responsible for the biggest fraud, while others objected towards capital punishment for Wawrzecki. The information we have on the dynamics of confirmed financial crimes does not provide a clear answer whether it was actually related to the severity of the punishments.